Pengaruh Mediasi Return on Equity dalam Hubungan antara Ukuran Perusahaan dan Penghindaran Pajak - Hutajulu, Aprilliani; Hutabarat, Francis (Universitas Pendidikan Ganesha, 2020)
This study was conducted to investigate whether Company Size and Return on Equity (ROE) have an influence on Tax Avoidance. The study uses quantitative data with 75 sample data in 15 banking sectors listed on the IDX in the financial statements from 2014-2018. Research samples were obtained from 15 companies in the banking industry listed on the IDX, namely: AGRO, BBCA, BBKP, BBNI, BBRI, BBTN, BBYB, BDMN, BJBR, BJTM, BMRI, BNGA, INPC, MCOR, and PNBN. To fulfill the hypothesis, statistical F test, T test and regression analysis are needed. The results showed that company size had no significant effect on tax avoidance and ROE had a significant effect on tax avoidance. It can be concluded that the existence of ROE fully mediates the influence of SIZE and Tax Avoidance